2004
DOI: 10.1021/jf030460m
|View full text |Cite
|
Sign up to set email alerts
|

Conformational Interpretation of Vescalagin and Castalagin Physicochemical Properties

Abstract: Vescalagin and castalagin are two diastereoisomers. The variability of their principal physicochemical properties, compared with their small structural differences, suggests important conformational variations. This study shows, experimentally, that vescalagin has a greater effect on polarity, oxidizability in solution, and thermodegradability than castalagin. Conformational analysis by molecular mechanics demonstrated that vescalagin was more hydrophilic and was more reactive to electrophilic reagents than ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
31
0
1

Year Published

2008
2008
2020
2020

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 39 publications
(35 citation statements)
references
References 26 publications
3
31
0
1
Order By: Relevance
“…Tannases generally act on gallotannins. However, in the particular case of ellagitannins, the information is scarce and confuse (Vivas et al 2004), mainly due to their chemical complexity and diversity. Saavedra et al (2005) reported that the production of EA has not been explored due to its high production cost and the great amount of subproducts generated as result of ellagitannin biodegradation.…”
Section: Resultsmentioning
confidence: 99%
“…Tannases generally act on gallotannins. However, in the particular case of ellagitannins, the information is scarce and confuse (Vivas et al 2004), mainly due to their chemical complexity and diversity. Saavedra et al (2005) reported that the production of EA has not been explored due to its high production cost and the great amount of subproducts generated as result of ellagitannin biodegradation.…”
Section: Resultsmentioning
confidence: 99%
“…However, despite the potential quantity of extractable ellagitannins in oak heartwood, the concentration in maturing spirits in cask is low . These results assume that ellagitannins in various reactions contribute to reduced concentration by chemical reactivity, such as oxidation . During spirit ageing, oxidation and hydrolysis/ethanolysis reactions participate in the transformation of polyphenols, such as ellagitannins.…”
Section: Discussionmentioning
confidence: 99%
“…In fact, 1 is reported to be more hydrophilic than 2 and with increased capacity to participate in hydrogen bonding due to the spatial organization of its OH at position C1 of the glycosidic chain. 24 In addition, the interaction can also comprise charge shielding effects and/or molecular rearrangements of the ligand/peptide complexes. Interestingly, ITC data is consistent with the ThT, WB and CD results by suggesting that the complexes formed between compound 1 and Aβ42 are more stable and energetically more favourable.…”
mentioning
confidence: 99%